Overall smoke control performance using naturally ventilated shafts in tunnel fires with multiple fire sources - Kun He; Ying Zhen Li; Haukur Ingason; Xudong Cheng (Underground Space)
This study investigates the overall smoke control performance using shafts in a naturally ventilated tunnel in the case of multiple fire sources. Detailed comparisons were also made with the corresponding single fire source scenarios. The results show that the interaction between multiple fire sources affects smoke control performance, resulting in a lower smoke layer height compared to the corresponding single fire scenario. For the multiple fire sources scenarios, the smoke layer height in the fire section first decreases and then keeps stable, as the fire center spacing increases. The smoke layer height in the fire section is 20%–25% lower than that in a single fire source scenario for a given total heat release rate. The minimum smoke layer height at the adjacent non-fire tunnel section is much lower than that in the fire section due to the disturbance of the first group of shafts. For a small tunnel fire such as a car fire, the critical safety distances for firefighters and evacuees increase as the fire source spacing decreases. For a large tunnel fire such as a bus fire, the effect of fire source spacing on the critical safety distance is limited, while the shaft interval plays an important role. The fire source spacing and the number of fire sources have limited influences on the smoke spread length due to the small differences in the induced air flow velocity and overall smoke exhaust rate through shafts. When the fire sources are located under one shaft, the number of shafts required for complete smoke exhaust is the least and the total smoke spread length is the shortest. For a given fire location, the smoke spread length increases significantly with an increasing shaft interval. This study contributes to the design of natural ventilation shafts in tunnels possibly with multiple fire sources.